Exploring Polymorphism: Flexibility and Code Reusability in Object-Oriented Programming - Ali, Hussein (Passer journal of basic and applied sciences (Online), 2024)
A key concept in object-oriented programming (OOP) is polymorphism, which enables objects or references to take on different forms depending on the situation. To allow for the creation of numerous sorts of objects, variables, and methods, it integrates ideas like virtual functions, function overriding, and function overloading. By enabling several implementations of the same function within parent classes, polymorphism promotes scalability and improves code clarity. Understanding how polymorphism is used in programming and how class objects may access and use it is crucial. This paper covers the idea of polymorphism, examines its uses, benefits, and drawbacks, and offers examples to show how it is used in OOP. Polymorphism allows for quick development, reuse of code, and flexibility in object-oriented programming paradigms.